The human, the orchid, and the octopus eaudiobook Exploring and conserving our natural world. - Cousteau, Jacques (Tantor Media, 2008)
Part adventure story, part manifesto, this is legendary ocean explorer Jacques Cousteau's passionate plea for sustaining life on earth. Explorer, diving pioneer, filmmaker, inventor, and activist, Jacques Cousteau was blessed from his childhood with boundless curiosity about the natural world. As the leader of fascinating, often dangerous expeditions all over the planet, he discovered firsthand the complexity and beauty of life on earth and undersea—and watched the toll taken by human activity in the twentieth century. In his magnificent last book, available for the first time in the United States, Cousteau describes his deeply informed philosophy about protecting our world for future generations. Weaving gripping stories of his adventures throughout, he and coauthor Susan Schiefelbein address the risks we take with human health, the overfishing and sacking of the world's oceans, the hazards of nuclear proliferation, and the environmental responsibility of scientists, politicians, and people of faith. Written over the last ten years of his life with frequent collaborator Schiefelbein, who also introduces the text and provides an update on environmental developments in the decade since Cousteau's death, this prescient, clear-sighted book is a remarkable testament to the life and work of one of our greatest modern adventurers.